Pengaruh Penggunaan Media Kartu Bergambar Bermuatan Cerita Rakyat Sasak: Cupak-Gerantang terhadap Kemampuan Membaca Kelas III SDN 2 Mataram - Gebby Fortuna; Moh. Irawan Zain; Baiq Yuni Wahyuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using picture card media incorporating local Sasak wisdom, specifically the Cupak-Gerantang story, on the reading ability of third-grade students at SDN 2 Mataram. This research employed a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The sampling technique used was non-probability sampling, specifically saturated sampling, in which all members of the population were included as the sample. Data were collected through tests to measure students’ reading ability and observations to support the research data. Data analysis was conducted using an independent sample t-test to identify differences between the experimental and control groups. The results showed that the average post-test score of the experimental class was 70.72, which was higher than that of the control class at 46.40. The hypothesis testing results indicated that the calculated t-value was greater than the t-table value (3.993 > 2.004), with a significance value (2-tailed) of 0.000 < 0.05. Therefore, Ha was accepted and Ho was rejected, indicating a significant effect of the use of the media on students’ reading ability.The effect size value of 1.06 falls into the large category, indicating that the use of picture card media based on Sasak local wisdom, specifically the Cupak-Gerantang story, has a strong effect on improving the reading ability of third-grade students at SDN 2 Mataram.